2013
DOI: 10.3390/molecules180911327
|View full text |Cite
|
Sign up to set email alerts
|

Dillapiole, Isolated from Peperomia pellucida, Shows Gastroprotector Activity against Ethanol-Induced Gastric Lesions in Wistar Rats

Abstract: Peperomia pellucida is a plant used in traditional medicine to treat gastric ulcers. Although this gastroprotective activity was reported, the active compounds have not been identified. Therefore, the aim herein was to identify the most active compound in the gastroprotective activity of P. pellucida using an ethanol-induced gastric ulcer experimental rat model. A gastroprotective effect was observed when the hexane and dichloromethane extracts were tested, with the higher effect being obtained with the dichlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
22
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 23 publications
4
22
0
1
Order By: Relevance
“…Pretreatment with the COX inhibitor, indomethacin (10 mg kg −1) did not modify the gastroprotective effect of calealactone B (Figure a), indicating that PGs are not involved in its mechanism of action. PGs were however found to be involved in the mechanism of action of carbenoxolone (Figure a) in agreement with literature reports (Rojas‐Martínez et al, ). The involvement of NO was also assessed.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Pretreatment with the COX inhibitor, indomethacin (10 mg kg −1) did not modify the gastroprotective effect of calealactone B (Figure a), indicating that PGs are not involved in its mechanism of action. PGs were however found to be involved in the mechanism of action of carbenoxolone (Figure a) in agreement with literature reports (Rojas‐Martínez et al, ). The involvement of NO was also assessed.…”
Section: Discussionsupporting
confidence: 92%
“…The involvement of NO was also assessed. NO is important in maintaining the integrity of the gastric mucosa via regulation of blood flow, angiogenesis and mucus secretion (Rojas‐Martínez et al, ). Pretreatment with L‐NAME, a nonspecific NOS inhibitor (70 mg kg −1 ) had no effect on the gastroprotective activity of calealactone B (Figure b).…”
Section: Discussionmentioning
confidence: 99%
“…1 Some of them have been isolated (particularly polyphenolic groups) including pellucidin A, 2 peperomins, secolignan, 3 xanthone patuloside A, 4 dillapiole, 5 chromene, 6 and quercetin. 7 Also, the herbs have also been reported to have potential pharmacological properties.…”
Section: Introductionmentioning
confidence: 99%
“…Rojas-Martinez. et al, 2013 [12] reported that dillapiole was identified as the most active compound in the dichloromethane extract and also reported the gastro protector activity of dillapiole. Ethanolic extract of P. pellucida accelerates fracture repairment in rats via stimulatory effects on osteoblast differentiation and mineralisation [13].…”
mentioning
confidence: 99%